2019
DOI: 10.1002/jcc.26045
|View full text |Cite
|
Sign up to set email alerts
|

WavePacket: A Matlab package for numerical quantum dynamics. III. Quantum‐classical simulations and surface hopping trajectories

Abstract: WavePacket is an open‐source program package for numerical simulations in quantum dynamics. Building on the previous Part I (Schmidt and Lorenz, Comput. Phys. Commun. 2017, 213, 223] and Part II (Schmidt and Hartmann, Comput. Phys. Commun. 2018, 228, 229] which dealt with quantum dynamics of closed and open systems, respectively, the present Part III adds fully classical and mixed quantum‐classical propagation techniques to WavePacket. There classical phase‐space densities are sampled by trajectories which fol… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(20 citation statements)
references
References 59 publications
(153 reference statements)
1
19
0
Order By: Relevance
“…For small numbers of sites, N ≤ 5, our results, obtained with ExciDyn, are in excellent agreement with values obtained from conventional, grid-based solvers for general Hamiltonians available within the WavePacket software package [43][44][45].…”
Section: B Softwaresupporting
confidence: 83%
“…For small numbers of sites, N ≤ 5, our results, obtained with ExciDyn, are in excellent agreement with values obtained from conventional, grid-based solvers for general Hamiltonians available within the WavePacket software package [43][44][45].…”
Section: B Softwaresupporting
confidence: 83%
“…The inset shows the labelling of the states as used in (5). The eigenenergies shown have been calculated using the WavePacket software package [56][57][58].…”
Section: Eigenenergies and Their Topologymentioning
confidence: 99%
“…By means of both analytic and numerical methods (Split-Operator FFT method via WavePacket software package [56][57][58]), we were able to carry out the population analysis of the resulting wavepackets as well as of the time-evolution of the observables such as orientation and alignment cosines and the kinetic energy of the planar rotor. Our analysis revealed that these observables mirror the intersections -avoided and genuine -of the eigenenergy surfaces spanned by the orienting and aligning parameters whose loci are characterized by an integer termed the topological index.…”
Section: Introductionmentioning
confidence: 99%
“…The first eigenvalue λ R 1 = 0 correspond to the steady state of the system, where L 1 = 1 [5,21]. Also, the eigenvalues with k > 1 satisfy the condition λ R k < 0 leading to dissipation terms ∝ e λ R k t in the general solution defined in equation (15). The eigenvalue with the largest negative real part (λ R N ) defines the envelope e λ R N t of the experimental observables (see figure 1-(b)).…”
Section: Markovian Quantum Master Equationmentioning
confidence: 99%
“…QuTIP library [10,11], the Quantum Mechanics Toolbox of Mathematica [12], and the Wave Packet open-source package of MATLAB [13,14,15], among others. In this work, we provide a simple tutorial to learn a route towards numerically solving a wide variety of complex quantum dynamics in MATLAB.…”
Section: Introductionmentioning
confidence: 99%